Demystifying a hexuronic acid ligand that recognizes Toxoplasma gondii and blocks its invasion into host cells - Subramani, Balamurugan; Shantamurthy, Chethan D.; Maru, Parag; Belekar, Meenakshi A.; Mardhekar, Sandhya; Shanmugam, Dhanasekaran; Kikkeri, Raghavendra (Organic & Biomolecular Chemistry, 2019)
Toxoplasma gondii is a ubiquitous eukaryotic pathogen responsible for toxoplasmosis in humans and animals. This parasite is an obligate intracellular pathogen and actively invades susceptible host cells, a process which is mediated by specific receptor-ligand interactions. Here, we have identified an unnatural 2,4-disulfated D-glucuronic acid (Di-S-GlcA), a hexuronic acid composed of heparin/ heparan sulfate, as a potential carbohydrate ligand that can selectively bind to T. gondii parasites. More importantly, the gelatin conjugated Di-S-GlcA multivalent probe displayed strong inhibition of parasite entry into host cells. These results open perspective for the future use of Di-S-GlcA epitopes in biomedical applications against toxoplasmosis.

Distinct metabolic states of a cell guide alternate fates of mutational buffering through altered proteostasis - Verma, Kanika; Saxena, Kanika; Donaka, Rajashekar; Chaphalkar, Aseem; Rai, Manish Kumar; Shukla, Anurag; Zaidi, Zainab; Dandage, Rohan; Shanmugam, Dhanasekaran; Chakraborty, Kausik (Nature Communications, 2020)
Metabolic changes alter the cellular milieu; can this also change intracellular protein folding? Since proteostasis can modulate mutational buffering, if change in metabolism has the ability to change protein folding, arguably, it should also alter mutational buffering. Here we find that altered cellular metabolic states in E. coli buffer distinct mutations on model proteins. Buffered-mutants have folding problems in vivo and are differently chaperoned in different metabolic states. Notably, this assistance is dependent upon the metabolites and not on the increase in canonical chaperone machineries. Being able to reconstitute the folding assistance afforded by metabolites in vitro, we propose that changes in metabolite concentrations have the potential to alter protein folding capacity. Collectively, we unravel that the metabolite pools are bona fide members of proteostasis and aid in mutational buffering. Given the plasticity in cellular metabolism, we posit that metabolic alterations may play an important role in cellular proteostasis.

Dietary supplementation of lactococcus lactis subsp. lactis BIONCL17752 on growth performance, and gut microbiota of broiler chickens - Navale, Vishwambar D.; Yadav, Rakeshkumar; Khilari, Ajinkya; Dharne, Mahesh; Shanmugam, Dhanasekaran; Vamkudoth, Koteswara Rao (Probiotics and Antimicrobial Proteins, 2024)
The rapid rise of antimicrobial resistance (AMR) is a global concern, being triggered by the overuse or misuse of antibiotics in poultry farming sector. We evaluated Lactococcus lactis subsp. lactis BIONCL17752 strain, and characterized its probiotic potential to endure hostile gastrointestinal conditions. Genome sequencing analysis revealed probiotics traits, and gene clusters involved in bacteriocins, lactococcin A, and sactipeptides production. The absence of genes for antibiotic resistance, virulence, and biogenic amine production indicates the potential of probiotic strain. The BIONCL17752 strain was explored for antibiotic-free feed supplement for growth promotor in broiler chicken. The feed supplemented with 4 x 109 CFU/kg of probiotic strain, in combination with various concentrations of fructooligosaccharides (FOS) 1.0, 2.5, and 5.0 kg/tonne in starter, grower, and finisher diets, respectively. A significant improvement of body weight 152 to 171 g/bird (p < 0.05), and a low feed conversion ratio (FCR) of 1.62, was achieved without using synthetic antibiotics for growth promotion. The results of biochemical, hematological, and histological examinations showed normal features, indicating that the treatment had no harmful effects on the bird's health. Reduced levels of cholesterol, triglycerides, high-density lipoprotein (HDL), and low-density lipoprotein (LDL) in serum are an indication of the health benefits for the treated birds. Microbial community analysis of fecal samples of poultry birds exhibited a higher abundance of Bacteroidetes, Firmicutes, Proteobacteria, Actinobacteria, and Fusobacteria. Probiotic treatment resulted in reduced Firmicutes and increased Bacteroidetes (F/B ratio) in the broiler's gut which highlights the benefits of probiotic dietary supplements. Importantly, the probiotic-fed group exhibited a high abundance of carbohydrate-active enzymes (CAZyme) such as glycoside hydrolases (GH), glycoside transferases (GT), and carbohydrate-binding module (CBM) hydrolases which are essential for the degradation of complex sugar molecules. The probiotic potential of the BIONCL17752 strain contributes to broilers' health by positively affecting intestinal microbiota, achieving optimal growth, and lowering mortality, demonstrating the economic benefits of probiotic treatment in organic poultry farming.
Keywords: Antibiotic growth promotor; Broiler chickens; Functional genome analysis; Growth performance; Gut microbiota; Lactococcus lactis subsp. lactis

Detection and variant characterization of lumpy skin disease virus from dairy cattle in India - Bajpai, Manali; Khilari, Ajinkya; Likhitkar, Bhagyashree; Musale, Pankaj; Jadhav, Santoshkumar; Dhanikachalam, Velu; Kakramkar, Payal; Bhave, Kaustubh; Swaminathan, Marimuthu; Joshi, Sachin; Shanmugam, Dhanasekaran (Virus Evolution, 2025)
The spread of a severe and often fatal form of lumpy skin disease (LSD) in cattle and water buffaloes has caused widespread mortality and morbidity of these animals in India. To track and understand the genetic changes occurring in the virus and to enable routine surveillance of the virus, multiplexed polymerase chain reaction (PCR) and sequencing methods were developed and validated in this study. Multiplexed nested PCR for LSD virus (LSDV) detection was optimized using skin lesion swabs and nasal samples collected from symptomatic and asymptomatic animals. For genotyping, overlapping PCRs to amplify the entire LSDV genome were developed and tested on field samples collected from the Maharashtra and Odisha states of India. Analysis of LSDV genomes from 41 field samples collected in 2022 and 2023 revealed the presence of highly conserved novel mutations. Phylogenetic analysis shows that a distinct genotype of LSDV has spread across India, which warrants genomic surveillance of the virus in the coming years to track the evolution and transmission of the virus. The non-invasive sample collection, detection, and genotyping methods described in this study can facilitate large-scale surveillance of LSDV in dairy animals.
Keywords: genotyping by sequencing; lumpy skin disease; multiplexed nested PCR; Oxford Nanopore technology; virus surveillance